The ash-1, ash-2 and trithorax genes of Drosophila melanogaster are functionally related. - Shearn, A. (Genetics, 1989)
Mutations in the ash-1 and ash-2 genes of Drosophila melanogaster cause a wide variety of homeotic transformations that are similar to the transformations caused by mutations in the trithorax gene. Based on this similar variety of transformations, it was hypothesized that these genes are members of a functionally related set. Three genetic tests were employed here to evaluate that hypothesis. The first test was to examine interactions of ash-1, ash-2 and trithorax mutations with each other. Double and triple heterozygotes of recessive lethal alleles express characteristic homeotic transformations. For example, double heterozygotes of a null allele of ash-1 and a deletion of trithorax have partial transformations of their first and third legs to second legs and of their halteres to wings. The penetrance of these transformations is reduced by a duplication of the bithorax complex. The second test was to examine interactions with a mutation in the female sterile (1) homeotic gene. The penetrance of the homeotic phenotype in progeny from mutant mothers is increased by heterozygosis for alleles of ash-1 or ash-2 as well as for trithorax alleles. The third test was to examine the interaction with a mutation of the Polycomb gene. The extra sex combs phenotype caused by heterozygosis for a deletion of Polycomb is suppressed by heterozygosis for ash-1, ash-2 or trithorax alleles. The fact that mutations in each of the three genes gave rise to similar results in all three tests represents substantial evidence that ash-1, ash-2 and trithorax are members of a functionally related set of genes.